Perbedaan Rasio Ukuran Mesiodistal Gigi (Bolton) Pada Maloklusi Klasifikasi Angle di SMPN 1 Salatiga Jawa Tengah - Anwar, Ervyanti Audri, Dwi Kurniawati, S.KG, MPH, drg. Suyadi (2015)
Width of mesiodistal tooth is one of the factors that need to be considered in orthodontic treatment. Mesiodistal tooth size discrepancy of the arch could be the causes of malocclusion. To estimate normal size of mesiodistal tooth used the ratio Bolton i.e. Bolton Overall Ratio (BOR) and Bolton Anterior Ratio (BAR). The purpose of this research is to know the difference between Bolton Overall Ratio and Bolton Anterior Ratio in relation to the first molar permanent tooth malocclusion of Angle classification at SMPN 1 Salatiga Central Java. This is an analytical observational with cross sectional design survey. Samples consisted of 51 people with fully erupted and complete permanent dentition form first molar to first molar who were registered by purposive sampling methode. The difference of ratio Bolton on malocclusion of Angle classification were tested using tests analysis of one-way Anova post hoc Bonferroni. Results of the analysis of BAR value was ranged between 72.41 and 90.14, with mean value 79.95±3.30. The lowest BAR was in Class II and the highest was in Class III. The BOR value was ranged between 87.54 and 97.38, with mean value 92.78±2.04. The lowest BOR was in Class II and the highest was in Class III. The result of one-way Anova analysis showed the p value in BAR toward malocclusion was 0,030, and BOR toward malocclusion was 0,165. It can be concluded that there was a difference means of Bolton Anterior Ratio (BAR) to malocclusion, but there is no difference means of Bolton Overall Ratio (BOR) to malocclusion. Analysis using post hoc Bonferroni showed that BAR differences was only in Class I and Class II Angle classification of malocclusion.